OPTIMIZATION OF PARAMETERS OF OPERATIONS OF DISINFECTION OF WASTE WATER OF FOOD PRODUCTION - N. V. Limarenko; L. A. Pudeyan (Современная наука и инновации)
Ensuring food security of the country directly depends on the effectiveness of food production technologies and the disposal of their waste. Unfortunately, the safe use of waste from most food industries is not possible without disinfection.